Safety and efficacy of taurine as an add‐on treatment for tics in youngsters. (11th November 2019) - Ding, L.; Yang, Z.; Liu, G.; Ran, N.; Yi, M.; Li, H.; Zhao, H.; Tang, L.; Cheng, H.; Zhao, J.; Zhang, Y.; Ji, X.; et al.
Abstract : Background and purpose: The pathophysiological model of tics generally describes disruption of γ‐aminobutyric acid transmission, and taurine is found to be an agonist of γ‐aminobutyric acid receptors. The study aimed to evaluate the safety and efficacy of taurine as an add‐on treatment for tics. Methods: Four hundred and four youngsters with tic disorders were randomly assigned to 12 weeks of either oral taurine or placebo. The Yale Global Tic Severity Scale was used to measure tic severity. The primary outcome measure was global severity scores reduced by more than 60% compared with baseline scores. Results: Three hundred and eighty‐two patients were successfully treated. At week 4, no significant differences were found in the treatment effect and the total occurrence of adverse drug reactions between the taurine and placebo groups. At week 12, the proportion of significant improvement in tics was significantly higher in the taurine group than the placebo group (53.4% with taurine versus 34.5% without taurine; relative risk 1.546; P < 0.001), and no group differences were found in the total occurrence of adverse drug reactions. Conclusions: Taurine is safe and effective for tics.